The ecological significance of arthropod vectors of plant, animal, and human pathogens. Issue 5 (May 2022) - Lefèvre, Thierry; Sauvion, Nicolas; Almeida, Rodrigo P.P.; Fournet, Florence; Alout, Haoues
Abstract : Vector management is a cornerstone in the fight against vector-borne pathogens. However, the impact on ecosystem functioning of reducing or eliminating arthropod vector populations remains poorly understood. Vectors are members of complex ecological communities, and recent studies suggest that their population suppression alters food web dynamics (bottom-up and top-down trophic cascades), inter- and intraspecific competition, and plant pollination. Other possible overlooked roles are also proposed. In this review, with examples from vectors of plant, animal, and human pathogens, we highlight that, although the ecological roles of most vector species might be redundant with other non-vector species, changes in vector abundance alter biotic interactions and, thus, are unlikely to be neutral in terms of ecosystem functioning. Highlights: Elimination of vector populations has immense potential for the management of vector-borne pathogens but poses significant ecological, environmental, societal, and ethical questions. Although vector biology has been studied primarily through the lens of vector management, recent efforts have sought to understand their ecological roles in ecosystems. While reductions in vector abundance alter biotic interactions through effects on food webs, competition, and pollination, it remains unresolved whether resulting impacts on biodiversity and ecosystem services are significant. Compared with the efforts devoted to evaluating the efficacy of vector management tools, there are few environmental impact assessments. Evaluating the ecological significance of vectors requires quantitative, long-term monitoring bringing together ecologists, botanists, entomologists, molecular biologists, and data scientists.